(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
The title “Scientific Society Ludovico Quaroni” of the journal appeared very intriguing to me. Because Quaroni (he was trained in an important Roman classical high school attended by all the children of the best and wealthy families of the best Roman bourgeoisie; he was also a schoolmate and friend of the writer Lidia Mazzoleni Storoni, translator of the famous Memorie di Adriano by Yourcenar), was essentially a “humanist”. Therefore, the adjective “scientific” refers to the humanistic-humanistic sciences and not to those of the so-called scientific disciplines. The humanistic root of Quaroni’s thought, and also, I would add, of doing, is repeatedly called into question by Lucio Barbera in several essays in this journal: starting with the surprise that Barbera (his pupil and later collaborator) experienced with regard to both the personal library of LQ rich in texts by classics and ancient and modern philosophers (the latter also published, and therefore read by him, in several European languages and beyond); and, obviously, the breadth of his knowledge of the international framework of the architecture of the time; and, finally, the classification criteria he adopted to order it and make it easy to consult (by the way: I discovered that those criteria were very similar to those I adopted (and kindly accepted and acquired) for my library which I donated to the Central Library of the Faculty of Valle Giulia). [...]